Transport Studies on Filler-doped Chitosan Based Polymer Electrolyte - S.R. Majid; N.H. Idris; M.F. Hassan; T. Winie; A. S. A. Khiar; A.K. Arof (Springer Nature Switzerland AG, 2024)
The room temperature conductivity of the chitosan complex containing 40 wt.% of salt increased from 6.02 x 10 6 Scm-~ to 2.10 x 10 5 Scm I after the addition of 1.0 wt.% aluminosilicate. Conductivity of the electrolyte is contributed from the charge carrier density and ionic mobility. The Rice and Roth model was applied in calculating the mobility, ~t and density of ions, n. The number density of ions, n, increases with temperature, while mobility, ~t decreases with increasing temperature. This work also suggests that the filler did not change the conduction mechanism of the charge carrier in chitosan-salt-filler complexes but helped to increase the conductivity value of the materials.